2010
DOI: 10.1149/1.3292284
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Improved Grain Conductivity of (Sm[sub 1−x]Y[sub x])[sub 2]Zr[sub 2]O[sub 7] Ceramics

Abstract: ͑Sm 1−x Y x ͒ 2 Zr 2 O 7 ͑0 Յ x Յ 0.5͒ ceramics were prepared by a solid-state reaction process at 1973 K for 10 h in air. ͑Sm 1−x Y x ͒ 2 Zr 2 O 7 ͑0 Յ x Յ 0.3͒ ceramics have a single phase of the pyrochlore-type structure, whereas ͑Sm 1−x Y x ͒ 2 Zr 2 O 7 ͑x = 0.4,0.5͒ exhibit a defective fluorite-type structure. The full width at half-maxima in the Raman spectra increase with increasing Y content, which indicates that the degree of structural disorder increases as the yttrium content increases. The electric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…At 1023-1173 K, the electrical conductivity of Sm 2 Zr 2 O 7 doped with 2.5-10 mol.% Mg at the Sm site is almost the same as undoped Sm 2 Zr 2 O 7 [18]. For (Sm 1−x Gd x ) 2 Zr 2 O 7 (0 ≤ x ≤ 1.0), (Sm 1−x Y x ) 2 Zr 2 O 7 (0 ≤ x ≤ 0.5) and (Sm 1−x Yb x ) 2 Zr 2 O 7 (0 ≤ x ≤ 1.0) systems, the electrical conductivity of pyrochlore-type compositions is clearly higher than that of defect fluorite-type compositions in the temperature range of 723-1173 K [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At 1023-1173 K, the electrical conductivity of Sm 2 Zr 2 O 7 doped with 2.5-10 mol.% Mg at the Sm site is almost the same as undoped Sm 2 Zr 2 O 7 [18]. For (Sm 1−x Gd x ) 2 Zr 2 O 7 (0 ≤ x ≤ 1.0), (Sm 1−x Y x ) 2 Zr 2 O 7 (0 ≤ x ≤ 0.5) and (Sm 1−x Yb x ) 2 Zr 2 O 7 (0 ≤ x ≤ 1.0) systems, the electrical conductivity of pyrochlore-type compositions is clearly higher than that of defect fluorite-type compositions in the temperature range of 723-1173 K [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, new A 2 Zr 2 O 7 -type oxides are of considerable scientific interests owing to variable cation radius ratios of r(A 3+ )/r(Zr 4+ ) and oxygen nonstoichiometry [7,[17][18][19][20][21]. The electrical conductivity of the pyrochlore-type Sm 2 Zr 2 O 7 was comparable to those of other oxide-ion conductors in the low-temperature region [17].…”
Section: Introductionmentioning
confidence: 99%
“…A significant increase in the electrical conductivity is found by suitable substitution of isovalent rareearth cations like Sm or Nd at the Gd site in defect fluorite-type Gd 2 Zr 2 O 7 [13,14]. For (Sm 1-x Yb x ) 2 Zr 2 O 7 (0 ≤ x ≤ 1.0) and (Sm 1-x Y x ) 2 Zr 2 O 7 (0 ≤ x ≤ 0.5) ceramics, the electrical conductivity of pyrochlore-type compositions is obviously higher than that of defect fluorite-type compositions in the temperature range of 723-1,073 K [15,16]. The electrical conductivity of Gd 2 (Sn 1-x Zr x ) 2 O 7 ceramics gradually increases with increasing zirconium content at identical temperature levels [17].…”
Section: Introductionmentioning
confidence: 99%
“…13 In independent works, Xia et al reported that degree of structural disorder in (Sm 1Àx Y x ) 2 Zr 2 O 7 , (Sm 1Àx Eu x ) 2 Zr 2 O 7 and (Sm 1Àx Mg x ) 2 Zr 2 O 7Àx systems gradually increases with an increase in the substitution of ions, which also inuenced the total ionic conductivity. [14][15][16] The transformation from ordered pyrochlore to a disordered defect uorite structure has been found to be inuential in the ionic conductivities of many other chemical systems like Y 2 Sn 2Àx Zr x O 7 and Nd 2Ày Ho y Zr 2 O 7 also. 17,18 As far as the conducting properties of pyrochlore type crystals are concerned, the 48f oxygen site is reported to play a crucial role in the ion diffusion mechanism in the lattice.…”
Section: Introductionmentioning
confidence: 99%